The Importance of Integrated Reporting in Value Creation (Intellectual Capital): A Theoretical Framework - Salehudin Bin Mohd. Simpol, Mohd. Salehudin Bin Mohd. Simpol; Noor Azli Bin Ali Khan, Mohd. (International Journal of Psychosocial Rehabilitation, 2020)
Corporate reporting has been many times evolved in order to meet the stakeholders’ expectations and needs. Now it is time for Integrated Reporting (IR). The wave of IR is coming to Malaysia as Security Commission (SC), Malaysian Institute of Accountants (MIA), Malaysian Accounting Standard Board (MASB) and more other non-profit organizations keep promoting the implementation of IR. The concept of IR is a reaction to the challenge companies’ face to create value and the related demands of users of corporate reports to receive decision useful information on the companies’ potential for future value creation this paper is a literature study on how IR is associated with the value creation of a business especially on intellectual capital (IC).